Conflict and Organizational Effectiveness: A Critical Analysis - Olanipekun, L. R.; Philips, Merai L. (Àgídìgbo: ABUAD Journal of the Humanities, 2019)
As there is nothing pre-determined about its course or development, it seems erroneous to view conflict from a negative perspective only, as destructive or dysfunctional. It is true that conflict may be uncomfortable, it may even be a source of problems, but it is absolutely necessary if change is to occur, if organizations are to survive and adapt. Organizational change and innovation does not just happen, it requires a stimulant. That stimulant is conflict. Administrators must accept the need to influence the developmental dynamics of a conflict, so that the parties’ attitudes and actions will lead to better coordination and a more appropriate interdependence. They must not seek to stifle or eliminate organizational conflict for that is hardly a realistic goal. As Rico has noted, an organization devoid of conflict “ may indicate autocracy, uniformity, stagnation and mental fixity.” It would also be protecting only the vested interests of the status quo. Administrators must accept and indeed occasionally encourage conflict, because change and other desirable consequences are products of conflict. The challenge administrators face is to utilize such conflict management techniques that would ensure that as a conflict passes from a latent to a manifest phase, it proceeds towards its potential and realizes its constructive values.